Human papillomavirus infection-related cancer risk for kidney transplant recipients during adult life can be reduced by vaccination during childhood and adolescence - Nailescu, Corina; Shew, Marcia L. (Frontiers in Pediatrics, 2022)
Malignancies are among the top three causes of patient death in pediatric and adult kidney transplant recipients, who experience more cancer compared to the general population, including human papillomavirus (HPV)-related anogenital and oropharyngeal cancers. Thus, preventing HPV infections in this population is critical. HPV-related vaccine trials have been shown to prevent HPV infection in immunocompetent individuals when the vaccine is given prior to viral exposure. In addition, more recent studies have demonstrated a true reduction in abnormal Pap smears and cervical cancers with use of HPV vaccine. Because HPV is sexually transmitted and often acquired soon after the onset of sexual activity, vaccination should ideally occur before sexual debut. This article briefly describes the epidemiology, pathophysiology and natural history of the HPV infection in both the general population and kidney transplant recipients, as well as its role in the development of HPV-related pre-cancerous lesions and cancers. Emphasis is given to the most effective primary prevention strategy, the HPV vaccination in kidney transplant candidates and recipients, and its particularities are compared to the general population. In addition, the article analyzes the various causes of suboptimal HPV immunization rates in kidney transplant candidates and recipients and discusses vaccination optimization strategies that can be applied during childhood and adolescence to reduce the burden of HPV-related disease states and cancer among adult kidney transplant recipients.